'How best do we survive?' : a modern political history of the Tamil Muslims - McPherson, Kenneth (New Delhi : Routledge, 2010)
On state of Muslims of South India in nineteenth century.
Includes bibliographical references (pages [223]-239) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Muslims -- India, South -- History -- 19th century; India, South -- History -- 19th century; Electronic books